Perbedaan Faktor Lingkungan Sosial dan Perilaku Seksual Pranikah pada Siswa SMA Perkotaan dan Perdesaan di Samarinda - Syaniah, Syaniah; Rachmawati, Annisa Nur; Permana, Lies; Rohmah, Nur; Agustini, Rina Tri (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. Based on the 2023 GSHS data, 7.1% of adolescents aged 13–17 in Indonesia have had sexual intercourse, of which 66.2% are male and 33.8% are female. Adolescent premarital sexual behaviour is influenced by internal and external factors. Differences in social determinants may lead to behavioural variations between groups within a population. Aim. To identify differences in peer influence, parental roles, and mass media (as social environmental factors), as well as premarital sexual behaviour among urban dan rural high school students in Samarinda Method. This comparative cross-sectional study involved 274 respondents, consisting of 206 respondents from three urban high schools and 68 from one rural high school. They were selected using simple random sampling. Data were analysed using the Mann-Whitney U test and the independent t-test (parental role). Result. A significant difference was found in peer influence (0.004) between urban and rural high school students, while no significant differences were found in parental role (0.864), mass media influence (0.713), and premarital sexual behavior (0.862) between urban and rural high school students in Samarinda. Researchers recommend the development of health education involving peer educators in schools and adolescent parenting education, especially in rural areas. Conclusion. The mean rank of the peer influence variable score is higher among high school students in rural areas than in urban areas in Samarinda.